Tribendimidine: mode of action and nAChR subtype selectivity in Ascaris and Oesophagostomum. - Alan P Robertson; Sreekanth Puttachary; Samuel K Buxton; Richard J Martin (Public Library of Science (PLoS), 2015)
The cholinergic class of anthelmintic drugs is used for the control of parasitic nematodes. One of this class of drugs, tribendimidine (a symmetrical diamidine derivative, of amidantel), was developed in China for use in humans in the mid-1980s. It has a broader-spectrum anthelmintic action against soil-transmitted helminthiasis than other cholinergic anthelmintics, and is effective against hookworm, pinworms, roundworms, and Strongyloides and flatworm of humans. Although molecular studies on C. elegans suggest that tribendimidine is a cholinergic agonist that is selective for the same nematode muscle nAChR as levamisole, no direct electrophysiological observations in nematode parasites have been made to test this hypothesis. Also the hypothesis that levamisole and tribendimine act on the same receptor, does not explain why tribendimidine is effective against some nematode parasites when levamisole is not. Here we examine the effects of tribendimidine on the electrophysiology and contraction of Ascaris suum body muscle and show that tribendimidine produces depolarization antagonized by the nicotinic antagonist mecamylamine, and that tribendimidine is an agonist of muscle nAChRs of parasitic nematodes. Further pharmacological characterization of the nAChRs activated by tribendimidine in our Ascaris muscle contraction assay shows that tribendimidine is not selective for the same receptor subtypes as levamisole, and that tribendimidine is more selective for the B-subtype than the L-subtype of nAChR. In addition, larval migration inhibition assays with levamisole-resistant Oesophagostomum dentatum isolates show that tribendimidine is as active on a levamisole-resistant isolate as on a levamisole-sensitive isolate, suggesting that the selectivity for levamisole and tribendimidine is not the same. It is concluded that tribendimidine can activate a different population of nematode parasite nAChRs than levamisole, and is more like bephenium. The different nAChR subtype selectivity of tribendimidine may explain why the spectrum of action of tribendimidine is different to that of other cholinergic anthelmintics like levamisole.